Students' Reading Responses to Tess of the d'Urbervilles, a Novel by Thomas Hardy - Yazid Basthomi; M.M. Amri; Kukuh P. Subagyo (Universitas Negeri Malang, 2016)
The study explored how students responded to Tess of the d'Urbervilles, a novel by Thomas Hardy. This study was a case study of an in-tact class of Prose I at the English Department, Universitas Negeri Malang. The data were collected from 25 students, and were in the form of students' papers, written in English, which were of the students' personal responses towards the novel. The study found that the students resorted to their re-ligius knowledge (ideology) when responding to the characters and subject matter of the novel. Students also developed certain kinds of feeling (emotion) as their religious ideology was challenged by that offered by the novel. The study also diclosed that the students' responses fell into the categories of thematic and empathetic. It follows that teachers of Literature need to make attempts to situate the students to arrive at higher level of responses: motivational, predictive, and critical-evaluative.